2015
DOI: 10.1002/anie.201504786
|View full text |Cite
|
Sign up to set email alerts
|

Design of Highly Photofunctional Porous Polymer Films with Controlled Thickness and Prominent Microporosity

Abstract: Porous organic polymers allow the integration of various π-units into robust porous π-networks, but they are usually synthesized as unprocessable solids with poor light-emitting performance as a result of aggregation-related excitation dissipation. Herein, we report a general strategy for the synthesis of highly emissive photofunctional porous polymer films on the basis of a complementary scheme for the structural design of aggregation-induced-emissive π-systems. We developed a high-throughput and facile metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 51 publications
(26 reference statements)
4
90
0
Order By: Relevance
“…Fore xample,i tw as demonstrated that high fluorescence quantum yields can be achieved upon rigidifying TPE-based species within metal-organic frameworks (MOFs). [14] Anion coordination to an oligourea-functionalized TPE derivative even gave a F F value as high as 41.3 %in concentrated solutions. [1e] Theintramolecular rotation of TPE has also been locked inside porous organic polymers to obtain an enhanced fluorescence quantum yield (F F )of40% in the solid state.…”
mentioning
confidence: 99%
“…Fore xample,i tw as demonstrated that high fluorescence quantum yields can be achieved upon rigidifying TPE-based species within metal-organic frameworks (MOFs). [14] Anion coordination to an oligourea-functionalized TPE derivative even gave a F F value as high as 41.3 %in concentrated solutions. [1e] Theintramolecular rotation of TPE has also been locked inside porous organic polymers to obtain an enhanced fluorescence quantum yield (F F )of40% in the solid state.…”
mentioning
confidence: 99%
“…Porous organic polymers (POPs) are a unique class of amorphous porous polymers that combine covalent π‐networks with inherent porosity. POPs are a class of emerging multifunctional materials and show outstanding properties and functions in various applications, such as gas storage, light emitting, catalysis, energy transfer and energy storage . They are robust in stability as a result of strong covalent bond‐linked network structure and can be synthesized using a variety of different π‐units.…”
Section: Porous Luminescent Films Based On Porous Organic Polymersmentioning
confidence: 99%
“…Although various π‐units have been utilized as monomers for the synthesis of π‐electronic POPs, their photofunctions are quite limited as a result of aggregation‐caused excitation energy dissipation. To solve this problem, a general strategy for designing highly emissive photofunctional POP films has been explored . The strategy for the structural design is to integrate three functional segments, including TPE core ( 38 ), twisted linkers and electropolymerizable N ‐substituted carbazole peripheral units into well‐defined porous π‐networks (Figure b, 39 ).…”
Section: Porous Luminescent Films Based On Porous Organic Polymersmentioning
confidence: 99%
“…a) Fluorescence quantum yields of monomer 10 in THF solution or as spin‐coated film, and of electrogenerated microporous P10 films of different thicknesses, b) degree of PL quenching of P10 films upon after interaction with various electron‐poor nitroarenes in acetonitrile, c) spectral PL changes of a P10 film (thickness of 5 nm) upon immersion in TNP solutions in acetonitrile (1 min), and d) reversibility of the TNP sensing approach ( P10 films, thickness 10 nm). Adapted with permission …”
Section: Films Of Carbazole‐based Microporous Polymer Networkmentioning
confidence: 99%